Hairy cell leukemia in father and son - (:unkn) unknown (HUMANA PRESS INC, 2003)
Hairy cell leukemia (HCL) is an uncommon B cell disorder, and familial HCL is rarely encountered among the first degree relatives of HCL patients. A father and son, both of whom developed hairy cell leukemia, is presented in this report. The HLA haplotype shared by the father and son was A2, B18, BW6, CW7, DR3, DR10, and DQ8. Among these haplotypes, HLA A2 and Bw6 have previously been reported.
Keywords: familial hairy cell leukemia.; HLA-LINKED DISEASE; 2 BROTHERS; EPIDEMIOLOGY; SIBLINGS